Development and Implementation of High-performance Circular Retroreflective Elements for Illumination of Highways and Transport Networks of Kyiv - Petrov, V.V.; Antonov, Ye.Ye.; Kryuchyn, A.A.; Shanoilo, S.M. (Science and Innovation, 2024)
Introduction. The introduction of advanced microprism retroreflective (cataphote reflectors) elements to illuminate highways contributes to improving road safety, especially, in the dark time. Therefore, the implementation of a competitive R&D project for the development of new types of cataphote reflectors is an important task. Problem Statement. As a result of a rapid increase in car flows and traffic intensity, improving traffic safety on highways due to the use of modern road signs and equipment is a relevant problem that needs to be urgently addressed. Purpose. The creation of new types of high-performance microprism cataphote reflectors for illuminating motor roads and highways. Materials and Methods. Computational methods for obtaining geometrical parameters of cataphote reflectors have been applied; diamond cutting technique has been developed for the formation of microrelief of retroreflective device. New elements have been manufactured using galvanic stamps with microprism retroreflective relief; the elements of cataphote reflectors have been assembled by ultrasonic welding. Results. Technological processes, precision equipment, and special equipment have been designed for manufacturing cataphote reflector cases from polycarbonate, forming light-reflective microprism structures from polymethylmethacrylate, assembling devices into a single optical block and sealing the final products by ultrasonic welding. Conclusion. A configuration has been designed and a trial batch of 500 pcs of curb circular cataphote reflectors with microprism round-shaped light elements has been manufactured. The devices have been installed by Kyivautodor road corporation at the crossings with most intensive traffic in Kyiv for trial run and preparation of recommendations for expanding the use of such devices in Ukraine.